Operando Visualization of Water Distribution in Gas Diffusion Media of PEFCs with an Optimized Neutron Grating Interferometer. Issue 6 (1st April 2020) - Siegwart, M.; Manzi-Orezzoli, V.; Valsecchi, J.; Harti, R. P.; Kagias, M.; Strobl, M.; Grünzweig, C.; Schmidt, T. J.; Boillat, P.
Abstract : We demonstrated the use of a neutron grating interferometer setup (nGI) with a significantly improved contrast-to-noise ratio of the operando dark-field (DF) contrast visualization of water in gas diffusion media (GDM). The nGI parameters were optimized in such a way that we could perform DF imaging of a fully operational fuel cell including two GDM layers (anode and cathode side). The DF contrast is sensitive to the size and shape of microstructures and is in principle not influenced by large water clusters present in flow field channels. Thus, DF imaging can be applied to analyze water present in GDM overlapping with channels, which is not possible by attenuation contrast imaging when the cell is placed perpendicular to the beam direction. In GDM regions overlapping with ribs the distinction of hydrophilic and hydrophobic areas is facilitated as well compared to attenuation contrast imaging. Finally, we show that disturbing artefacts introduced by moving water clusters in the channels are considerably reduced by applying a golden ratio phase stepping scan strategy.